Left-sided giant adrenal myelolipoma secreting catecholamine - Sujatha Udupa; M Usha; R N Visweswara; M G Desai (Wolters Kluwer Medknow Publications, 2012)
Adrenal myelolipoma (AML) is a rare benign tumor composed of mature adipose and hematopoietic tissue. Most of these patients are asymptomatic and the tumors are non-secreting. We present a case with a large functional adrenal myelolipoma, wherein the patient was hypertensive and biochemistry revealed increase in 24 hours urinary Vanillylmandelic Acid (VMA), a metabolite of catecholamine. The mass was removed surgically and diagnosed as adrenal myelolipoma on histopathological examination. Both his blood pressure and urinary VMA returned to normal following surgery, which suggested that the mass was functioning and was secreting catecholamine. To the best of our knowledge, a catecholamine secreting adrenal myelolipoma has been reported in the literature only once previously. The association of hypertension and adrenal myelolipoma may not be entirely coincidental, as it may be associated with secreting catecholamine, as seen in our case. We also review the literature on functioning adrenal myelolipoma.